2018
DOI: 10.1007/s11665-018-3712-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Post-treatments on the Microstructure of EBM-Built Alloy 718

Abstract: Electron beam melting (EBM) of Alloy 718 is of rapidly growing interest as it allows cost-effective production of complex components. However, the inherent flaws in the component in as-built state are of concern in view of the severe working conditions in which Alloy 718 components typically operate. The present work entails an investigation of changes in microstructure that accompany some post-treatments that are being widely considered to address defects in EBM processed Alloy 718. The effect of two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…This value is close to the reported peak hardness (~490 kgf/mm 2 ) of Alloy 718 [10]. Previous studies on EBM Alloy 718 have also reported an increase in hardness in the as-built condition from 410 kgf/mm 2 to 470 kgf/mm 2 after aging [32][33][34]. Thus, the foregoing results amply reveal that, regardless of the vastly different defect content in the as-built condition, the final post-treated condition exhibits a very similar density (Figure 3), phase constitution in terms of δ phase and γ" phase distribution ( Figures 5 and 6), as well as microhardness values (Figure 7).…”
Section: Resultssupporting
confidence: 88%
“…This value is close to the reported peak hardness (~490 kgf/mm 2 ) of Alloy 718 [10]. Previous studies on EBM Alloy 718 have also reported an increase in hardness in the as-built condition from 410 kgf/mm 2 to 470 kgf/mm 2 after aging [32][33][34]. Thus, the foregoing results amply reveal that, regardless of the vastly different defect content in the as-built condition, the final post-treated condition exhibits a very similar density (Figure 3), phase constitution in terms of δ phase and γ" phase distribution ( Figures 5 and 6), as well as microhardness values (Figure 7).…”
Section: Resultssupporting
confidence: 88%
“…These results corroborate the observations of Balachandramurthi et al [9], who have also reported the grain growth after HIPing of EBM Alloy 718 at 1200°C to be mainly restricted to the contour region. In other studies employing HIPing at 1200°C, too, extensive grain growth in the hatch region was observed [12,26].…”
Section: Grain Structurementioning
confidence: 83%
“…Prior to HIPing, all the specimens were subjected to ultrasonic cleaning. Here it should be mentioned that prior work by authors has already established uniformity in the EBM build [26]. The selection of conditions for HIP1 (1120°C, 100 MPa, 4 h) and HIP2 (1185°C, 100 MPa, 4 h) was based on the suggestions in the ASTM F3055 standard for powder bed fusion built Alloy 718 [19].…”
Section: Thermal Post-treatmentsmentioning
confidence: 99%
“…This has been an important motivation behind this study. Although prior work by the authors has involved investigation of aspects related to uniformity in a typical EBM Alloy 718 build, [23] inclusions and precipitates in as-built and post-treated material, [24] extent of defect closure during HIPing in builds with intentionally introduced defects, [25] etc., the response of hatch and contour regions to identical post-treatments remains not fully investigated.…”
Section: Introductionmentioning
confidence: 99%